Teachers’ Strategies in Teaching Reading Comprehension through E-learning Platform during the Pandemic - Adhe Syahputra; Marzul Hidayat; Bunga Ayu Wulandari (Edukasi, 2022)
This study was aimed to explore EFL teachers' strategies in teaching reading comprehension through an e-learning platform at one public senior high school in Jambi. This study employed a qualitative research design which was a case study. The study utilized two data collection techniques: observation and interview. Two teachers of English were involved in this study. All of the data were analyzed using four significant stages of analysis: coding, data reduction, data display and concluding. The frequency of observations was grounded on reading teaching material taught by participants. This study revealed that the teachers used three strategies to teach reading comprehension through virtual e-learning. The strategies were translating, SQ3R (Survey, Question, Read, Recite, Review) and QARs (Question-Answer Relationships). The findings also revealed teachers' reasons for selecting those strategies. Generally, their reasons were (1) to help the students to comprehend the text and (2) to relate students' real-life experience and prior knowledge with the text. The time limitation of lesson hours caused by COVID 19 also affected teachers' decisions in selecting the strategies.